2018
DOI: 10.1038/s41467-018-07328-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dynamics of coherent Ising machines through simulation of large-scale 2D Ising models

Abstract: Many problems in mathematics, statistical mechanics, and computer science are computationally hard but can often be mapped onto a ground-state-search problem of the Ising model and approximately solved by artificial spin-networks of coupled degenerate optical parametric oscillators (DOPOs) in coherent Ising machines. To better understand their working principle and optimize their performance, we analyze the dynamics during the ground state search of 2D Ising models with up to 1936 mutually coupled DOPOs. For r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…3b). It is interesting to note here that these domain evaporation dynamics are likewise observed in DOPO-based CIMs 17,24 .
Fig. 3Spin dynamics during a ground state search in a square lattice.
…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…3b). It is interesting to note here that these domain evaporation dynamics are likewise observed in DOPO-based CIMs 17,24 .
Fig. 3Spin dynamics during a ground state search in a square lattice.
…”
Section: Resultssupporting
confidence: 54%
“…Based on this, various types of CIMs have been proposed that implement Ising spin networks with bistable coherent optical states, such as coupled lasers 7,14 and degenerate optical parametric oscillators (DOPOs) 8 . Current state-of-the-art CIMs based on DOPOs have demonstrated their ability as global optimizers for various large-scale problems 11,1517 . By taking advantage of the large bandwidth of optical systems, they can operate at high speed and have shown speed-ups over conventional algorithms 11,18 .…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the fiber-based DOPO system has a T sol = 3.3 ms for solving cubic MAX-CUT problems and T sol = 2.3 ms for dense MAX-CUT with N = 100 23 , suggesting that the spatial-multiplexing approach offers promise for accelerating the computing time of an Ising model. As the number of DOPOs in the network increases, the anneal time that corresponds to the pump turn-on time must be controlled to slow down the DOPO dynamics to prevent freeze-out effects that prevent the system from reaching the ground-state solution 23 , 35 . More specifically for our system of microresonator-based DOPOs, it has been reported elsewhere that the rate at which the DOPOs are tuned into resonance is a decisive parameter that determines the success probability of finding the ground-state solution (see Supplementary Note 8 ) 41 .…”
Section: Resultsmentioning
confidence: 99%
“…These demonstrations have utilized a time-multiplexed DOPO system using a 1-km-long fiber ring cavity to simulate the ground state of the Ising model 20 , 21 . In addition, extensive experimental and theoretical analysis has been done to characterize the potential performance of such systems 23 , 33 35 . Furthermore, alternative approaches towards a coherent Ising machine, such as opto-electronic oscillators with self-feedback 24 26 and spatial light modulation 27 , 28 , has been demonstrated and an approach using a dispersive optical bistability has been proposed 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing the common terminology from condensed matter, a single parametric oscillator can be viewed as a classical two-level system (spin-1/2, or Ising spin). Based on this analogy, it has been recently suggested that coupled parametric oscillators can be used to simulate chains or networks of Ising spins [30][31][32][33][34][35][36][37][38][39][40]. The Ising simulation relies on the inherent mode competition and positive feedback within the oscillators to find the most efficient (coupled-mode) oscillation, which can reflect the groundstate configuration of the corresponding Ising model (under certain assumptions): A set of optical parametric oscillators can therefore represent a set of independent spin-1/2 systems, where coupling of the optical field between the oscillators gives rise to a coupled network of spins.…”
mentioning
confidence: 99%